4(2x-1)-6x(3x+1)=4-6x

Simple and best practice solution for 4(2x-1)-6x(3x+1)=4-6x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2x-1)-6x(3x+1)=4-6x equation:


Simplifying
4(2x + -1) + -6x(3x + 1) = 4 + -6x

Reorder the terms:
4(-1 + 2x) + -6x(3x + 1) = 4 + -6x
(-1 * 4 + 2x * 4) + -6x(3x + 1) = 4 + -6x
(-4 + 8x) + -6x(3x + 1) = 4 + -6x

Reorder the terms:
-4 + 8x + -6x(1 + 3x) = 4 + -6x
-4 + 8x + (1 * -6x + 3x * -6x) = 4 + -6x
-4 + 8x + (-6x + -18x2) = 4 + -6x

Combine like terms: 8x + -6x = 2x
-4 + 2x + -18x2 = 4 + -6x

Solving
-4 + 2x + -18x2 = 4 + -6x

Solving for variable 'x'.

Reorder the terms:
-4 + -4 + 2x + 6x + -18x2 = 4 + -6x + -4 + 6x

Combine like terms: -4 + -4 = -8
-8 + 2x + 6x + -18x2 = 4 + -6x + -4 + 6x

Combine like terms: 2x + 6x = 8x
-8 + 8x + -18x2 = 4 + -6x + -4 + 6x

Reorder the terms:
-8 + 8x + -18x2 = 4 + -4 + -6x + 6x

Combine like terms: 4 + -4 = 0
-8 + 8x + -18x2 = 0 + -6x + 6x
-8 + 8x + -18x2 = -6x + 6x

Combine like terms: -6x + 6x = 0
-8 + 8x + -18x2 = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-4 + 4x + -9x2) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-4 + 4x + -9x2)' equal to zero and attempt to solve: Simplifying -4 + 4x + -9x2 = 0 Solving -4 + 4x + -9x2 = 0 Begin completing the square. Divide all terms by -9 the coefficient of the squared term: Divide each side by '-9'. 0.4444444444 + -0.4444444444x + x2 = 0 Move the constant term to the right: Add '-0.4444444444' to each side of the equation. 0.4444444444 + -0.4444444444x + -0.4444444444 + x2 = 0 + -0.4444444444 Reorder the terms: 0.4444444444 + -0.4444444444 + -0.4444444444x + x2 = 0 + -0.4444444444 Combine like terms: 0.4444444444 + -0.4444444444 = 0.0000000000 0.0000000000 + -0.4444444444x + x2 = 0 + -0.4444444444 -0.4444444444x + x2 = 0 + -0.4444444444 Combine like terms: 0 + -0.4444444444 = -0.4444444444 -0.4444444444x + x2 = -0.4444444444 The x term is -0.4444444444x. Take half its coefficient (-0.2222222222). Square it (0.04938271604) and add it to both sides. Add '0.04938271604' to each side of the equation. -0.4444444444x + 0.04938271604 + x2 = -0.4444444444 + 0.04938271604 Reorder the terms: 0.04938271604 + -0.4444444444x + x2 = -0.4444444444 + 0.04938271604 Combine like terms: -0.4444444444 + 0.04938271604 = -0.39506172836 0.04938271604 + -0.4444444444x + x2 = -0.39506172836 Factor a perfect square on the left side: (x + -0.2222222222)(x + -0.2222222222) = -0.39506172836 Can't calculate square root of the right side. The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 16+5z=1 | | x=lx-6l | | 2x-3=7x+9 | | (q-3)*5=15 | | 10x-8=9x+6 | | sen*6x+cos*4x+sen*4x+cos*6x=0 | | -2a=-9 | | x^4-3x^3-2x^2-2x+12=0 | | -11+7m+16+(-9m)= | | (-7x-4)(2x+8)= | | 2ln(x)+2x^2+7=0 | | 14x=14x+12 | | 2(x+1)=-3x-10 | | 4x-2(x+1)= | | 4x-12=28-x | | Y=-3.8x+7.1 | | 7v+27=-5(v-3) | | 420t-6t^2=3675 | | 3a*2+yx=7 | | 6(x-4)=8x-28 | | 4*(x+1)=2*(5-3x) | | 6+3a= | | 7u-36=3(u-8) | | t^2-60t=-450 | | t^2+60t=-450 | | -3*-3+6+2= | | 14(6x+16)= | | 3*3+6+2= | | 5+7(2b-2b)=5 | | y(25+-.75y)=350 | | x^2+y^2+6x-14y+42=0 | | 42-21x=63-7y |

Equations solver categories